Sunscreen Lotion Base on Ethanol Extract of Balakacida (Chromolaena odorata) Leaves to Prevent Skin Cancer - I Gusti Made Budiana (Journal of Health and Behavioral Science, 2022)
Cases of skin cancer caused by exposure to ultraviolet rays continue to increase from year to year. So far, the prevention of skin cancer uses inorganic sunscreen lotion, only a few use ingredients from plants. In this research, a sunscreen lotion formula was made using the basic ingredients of the balakacida plant extract (Chromolaena odorata). The research was carried out in 4 stages namely; (1) preparation of balakacida leaf samples, (2) preparation of extracts, (3) preparation of lotion, (4) testing of the quality of sunscreen lotion including; sun protection factor (SPF), homogeneity, spreadability and pH values. Testing the SPF value using the ultra violet spectroscopy method and testing the pH using a pH meter. The results showed that the ethanol extract of balakacida leaves was 21.5% and the sunscreen lotion was a light green semi-solid substance. The results of the lotion quality test showed that the value of SPF, homogeneity, spreadability and pH values were respectively 26.95 at a concentration of 10%, homogen, 5.6 cm and 6.7. Based on the results obtained, it can be concluded that a sunscreen lotion made from balakacida leaves is very good to be developed as a sunscreen lotion to prevent skin cancer.